Transformation of university college to university - Sara Asmawati, Shariffuddin (2018)
The transformation of university colleges to universities is one of the efforts to achieve the national vision and mission towards becoming a developed country. The transformation process involves various procedures and many parties in particular the academics. The work pressure to fulfill the requirements and to achieve the transformation objectives leaves huge impacts on them. Therefore, the study was conducted to explore the academics’ understanding, the challenges they experience in the transformation process and types of supports provided by the management to manage the challenges. Mixed-methods approach was employed with a single case study as the primary qualitative approach followed by a survey to obtain data from a sample of a university college in Malaysia. Whilst, for qualitative method, twelve academics were interviewed and various documents were collected from five departments; for quantitative method, a set of questionnaire was distributed via e-mail to the academics in data collection process. Thematic analysis and descriptive statistics were used to analyse data obtained for the study. The findings indicate that the academics understood the transformation process and the challenges experienced in the process. Apart from that, the findings also reveal that twelve types of challenges were experienced by the academics in the transformation process including teaching and learning, supervision, research, publication and commercialization, consultation, community program, working culture and environment, management, funding, institution, academic identity and job security. Furthermore, the research discovers that the academics required supports from the management of the university college to realize the transformation process. In addition, the research proposes a model or framework as a guideline for transforming university colleges to universities. Finally, the findings provide theoretical, methodological and practical implications that contribute not only to the study of transformation of university college to university but also in promulgating relevant policies pertaining to the transformation of higher education institutions in Malaysia in general.